Against all odds World Food Prize Laureate Dr. Akinwumi Adesina and his drive to feed Africa - Hesser, Leon. (Bloomington AuthorHouse, 2019)
This book is about the journey of Dr. Akinwumi Adesina and his mission to end poverty in Africa. Growing out of poverty and witnessing hardships of being poor, he set his life mission as giving hope to millions of the poor in rural Africa. A globally respected economist with decades of experience working in some of the worlds' leading organizations including the Rockefeller Foundation and global agricultural research centers, Dr. Adesina's work and passion continues to guide and shape global efforts on transforming Africa's agriculture to create wealth for its farmers. As Nigeria's Minister of Agriculture, he led bold reforms that cut out corruption and helped to lift over 15 million farmers out of poverty within four years. Awarded the World Food Prize in 2017 for his work, Dr. Adesina is relentless and selfless, donating his
Includes bibliographical references (pages 218-221)
Keywords: Adesina, Akinwumi A